A supremely bad idea : three mad birders and their quest to see it all - Dempsey, Luke; Dempsey, Luke. (New York : Bloomsbury, 2009)
An unlikely birder traces his indoctrination into the hobby by a pair of obsessive fellow enthusiasts and their zealous nation-wide search for rare and noteworthy species, in an account that describes their haphazard encounters with human and natural challenges.
Keywords: Bird watching -- United States -- Anecdotes